Urgensi Pembaruan Regulasi Teknologi Informasi di Era Disrupsi Digital: Potret Kegamangan Hukum Positif Indonesia dalam Merespons Perubahan Sosial - Gilang Rizki Aji Putra (UIN Jakarta, 2020)
Digital disruption has created new realities that existing technology laws cannot fully address. This study highlights the need to update regulations in Indonesia to keep pace with rapid technological developments. It finds that many current laws are outdated and unable to regulate innovations such as artificial intelligence, the Internet of Things (IoT), and cross-border digital payments. Without adaptive reforms, Indonesia risks legal gaps that threaten its digital sovereignty. The study concludes that regulatory reform should be flexible and adopt an agile governance approach, while strengthening oversight institutions. Keywords: Digital Disruption, Regulatory Reform, Artificial Intelligence, Agile Governance, Digital Sovereignty